Representações da monstruosidade na caracterização das personagens do filme freaks (1932) - BARROS, Ivon Mendes de (2017)
This research develops a film analysis of Freaks (Tod Browning, 1932), in order to observe the representations of monstrosity in the visual characterization of the characters. This characterization, examined here, is the design of the appearance of the fictional being; which includes the physical profile of the performer, the costumes, hair, makeup and props, as well as the gesture and facial and body expression of the person who embodies the character, in addition to lighting, framing, camera effects and editing. In this way, the characterization prints in the image representations that reveal characteristics of the character and the situations that she experiences in the plot. Such representations can mean or symbolize various things, and this text observes the signs of monstrosity. The monster is understood here as Luiz Nazário presents in The Nature of Monsters (1998); a threatening and cruel being, which exists in opposition to humanity, which is the "other" of the human being. It is observed that several narrative structures of the monster exist in the film of Browning and some personages of Freaks present a visual that builds the monstrous mask, independent of the corporal profile. In 1932, when Browning released his film, there were still public exhibitions in which people with physical disabilities were presented as human monsters, and several interpreters of the film were attractions of this type of exhibition. In most of the film, while two characters with ordinary bodies assume morally monstrous attitudes, the uncommon ones present a cordial daily practice and a characterization similar to the others; only at the end of the plot, the uncommon ones present a more monstrous visuality. In the appearance of the characters of Freaks, Browning confronts moral principles of the audience and sows reflections on human diversity, the identity of each person and the exercise of otherness.